Perubahan Fisik berhubungan dengan Kecemasan Wanita Menghadapi Premenopause - Marzah Susanti; Baiq Nova Aprilia Azamti; Fidiya Rizka (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Premenopause is a trasitional period that occurs several years before menopause and includes changes from ovulatory cycles to anovulatory cycles with signs of irregular been felt before.Purpose: This study aims to determine the correlation between physical changes and the anxiety of women facing premenopause.Method: This study used a cross-sectional approach. The population was all premenopause women in Brang Kolong Village, Plampang District, sumbawa Regency. The total population was 102, and using the accidental sampling technique, 50 of them were taken as samples. The data was analyzed using the Spearman Rank method.Results: The results show that 29 or 58% respondents were elementary school graduates, and 39 or 78% samples had a job. In addition, premenopause women who experienced a few physical changes, 28 (56%), experienced severe anxiety.Conclusion: Based on the statistical analysi Ha was accepted. Furthermore, the result of the analysis using the Spearman Rank using SPSS Version 23 showed a p-Value of 0.005. This means that there was a correlation between physical changes and anxiety of women in Brang Kolong Village, Plampang District, Sumbawa Regency facing premenopause.